Accuracy of 3D Printer Technologies Using Digital Dental Models - Şule Gökmen; Serkan Görgülü; Kübra Gülnur Topsakal; Gökhan Serhat Duran (Turkish Journal of Orthodontics)
Objective: This study aimed to compare the manufacturing accuracy of different printing techniques - Stereolithography (SLA), Digital Light Processing (DLP), and PolyJet-using digital dental models. Methods: The study included cast models of 30 patients aged between 12 and 20 years. The selected models were scanned using an intraoral scanner, and surface topography format files were obtained. The models were produced from 3D printers with SLA, DLP, and PolyJet technology and scanned with an intraoral scanner. The digital files of the reference and printed models were superimposed with reverse engineering software. Root mean squared (RMS) values and point registration differences were evaluated. Furthermore, digital mesiodistal measurements of the teeth were taken to determine the point registration deviation values. Descriptive statistics were used to evaluate the measurements. ANOVA was used to evaluate differences between normally distributed data. In addition, a box plot was used to show the variability in the measurements, and the Bland-Altman test was used to examine the agreement between the measurements. Results: According to the digital superimposition data of DLP-SLA-PolyJet technologies, PolyJet had the smallest RMS (0.145±0.10 mm), followed by DLP and SLA (0.161±0.12 mm and 0.345±0.23 mm, respectively). In the mesiodistal dimensional measurement evaluations, there was no statistically significant difference (p>0.05) between the averages of the main reference and DLP, PolyJet, and SLA measurements for all teeth. Conclusion: According to the results of this study, all three production technologies are clinically usable at the model production stage. However, SLA was found to be less accurate than DLP and PolyJet.